1975
DOI: 10.1021/ic50145a011
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation-state and electron-transfer properties of mixed-valence 1,1'-polyferrocene ions

Abstract: AIC405166'The oxidation state properties of the compounds biferrocene, 1 ,I '-terferrocene, and 1,l'-quaterferrocene have been investigated using electrochemical techniques. In the polymeric compounds all of the ferrocene groups are oxidizable to ferricenium at distinct potentials. The values of the potentials can be predicted in some cases using ferrocenyl substituent effects. Partial oxidation gives a series of discrete mixed-valence ions. The mixed-valence ions can exist as a series of oxidation state isome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
1

Year Published

1980
1980
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(70 citation statements)
references
References 4 publications
3
66
1
Order By: Relevance
“…Recent NMR studies of the dihydro-reduced form of ladderstructured polyquinoxaline oligomer also have showed that it has indeed a structure with two protons added in the same pyrazine ring, i.e., a so-called benzoid structure and not a quinonoid structure with two protons added in the different pyrazine rings [29]. The above-mentioned results show that the pyrazine rings in DAP, TAP and HAT are reduced ring by ring in 2e À /2H þ reactions and they seem to act as the redox centers of the individual molecules as the metal ions in the p-conjugated polynuclear metal complexes [1][2][3][4][5][6]9,10].…”
Section: The Number Of Protons Involved In the Reductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent NMR studies of the dihydro-reduced form of ladderstructured polyquinoxaline oligomer also have showed that it has indeed a structure with two protons added in the same pyrazine ring, i.e., a so-called benzoid structure and not a quinonoid structure with two protons added in the different pyrazine rings [29]. The above-mentioned results show that the pyrazine rings in DAP, TAP and HAT are reduced ring by ring in 2e À /2H þ reactions and they seem to act as the redox centers of the individual molecules as the metal ions in the p-conjugated polynuclear metal complexes [1][2][3][4][5][6]9,10].…”
Section: The Number Of Protons Involved In the Reductionmentioning
confidence: 93%
“…With the conjugation interaction, the redox reaction of N-nuclear compounds will have N pairs of redox peaks, when N equals 2, 3 or 4 [1]. This kind of electrochemical behavior for both linear and ring complexes has been studied by Aoki et al [2][3][4][5][6] by means of a quantum chemistry approach.…”
Section: Introductionmentioning
confidence: 99%
“…The electron interaction or the charge delocalization of multiferrocenyl derivatives have been explored in terms of investigating electron transfer numbers of each ferrocenyl unit in the molecules [4][5][6]. However, when ferrocenyl units were assembled into one molecule, the electron transfer processes of multiferrocenyl derivatives became unintelligible due to the charge transfer became more complicated [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed , for polyferrocertes each of the ferrocene centers is separately oxidizable to ferricinium at a distinct potential (12). Because the interaction between sites is potentially so strong, clusters with direct metal-metal interaction or with single-atom bridges are expected , and found , to yield a large number of mixed-valence materials.…”
mentioning
confidence: 99%
“…The implications of this rela-• tion with respect to the existence of mixed-valence species will be discussed below. Figure 2 shows the cyclIc volca agram of biferrocene (12).…”
mentioning
confidence: 99%